PENGARUH MEDIA PEMBELAJARAN KARTU HURUF DAN KARTU GAMBAR TERHADAP HASIL BELAJAR SISWA PADA MATERI MEMBACA PERMULAAN DI SD - Lala Dwi Putri; Ramanata Disurya; Juaidah Agustina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to produce learning outcomes using letter cards and picture cards as learning media that are valid, practical, and effective for early reading. The type of research used is the effect of letter cards and picture cards as learning media. This study uses tests as instruments. The research technique used to analyze the data is the experimental research method with a quasi-true experimental design. The data analysis technique used in this study is the paired sample t-test. The results of this study indicate that there is an effect of using letter cards and picture cards on student learning outcomes in early reading at SD Negeri 80 Palembang in 2025, with the posttest average scores being 60% for the control class and 80% for the experimental class. The results of the hypothesis testing were obtained based on calculations, yielding a t-calculated value of 22.792 and a t-table value of 1.680. Since t-calculated = 22.792 > t-table = 1.680, this means that H_a is accepted and H_0 is rejected